O Turismo ecológico sustentável e a autoconsciência do homem contemporâneo: uma abordagem filosófica da questão ambiental - Blanco, Enrique (Boletim Técnico do Senac, 2003)
The concept and the ideal of nature have changed throughout history. Presently, consumption logic has guided human interventions in nature, considered as an inexhaustible source of resources. Ecological tourism, taken as one of those interventions, lacks the critical space needed for reflection on its practices. The philosophy of nature or ecophilosophy can help in this process, contributing with philosophical reasoning to mediate the ground between humankind, tourism, and nature.